BQ-123, a specific endothelin (ETA) receptor antagonist, prevents ischemia-reperfusion injury in kidney transplantation - (:unkn) unknown (My University, 1996)
We studied the effects of the specific endothelin (ETA) receptor antagonist, BQ-123, on reperfusion injury in a rat model of kidney transplantation. First, Sprague-Dawley rats were divided into three groups: a sham nephrectomy (SNEPH), an autotransplantation (AUTO-Tx), and an allotransplantation (ALLO-Tx) group. In a fourth group, ALLO-Tx + BQ, allografts were flushed with 20 micrograms BQ-123 containing cold Ringer's lactate before transplantation. For the allograft groups, kidneys from white Wistar albino rats were transplanted into allogeneic Sprague Dawley recipients. Grafts were allowed 120 min of reperfusion after 40 min of cold ischemia. ET-1,2 plasma concentrations in the renal venous blood, and kidney tissue prostaglandin (PG) E2 and leukotriene (LT) B4 levels were studied. Diene conjugates (DC), hydroxyalkanals (HAA), hydroxyalkenals (HAE) and malondialdehyde (MDA) levels, as the products of lipid peroxidation, and protein carbonyls (PC) and protein sulphydryls (PS), as the parameters of protein oxidation, were also analyzed in the kidney tissue. Plasma ET concentrations increased significantly in the AUTO-Tx and ALLO-Tx groups (P < 0.05 and P < 0.01, respectively) but this increase was reversed in the ALLO-Tx + BQ group. None of the lipid peroxidation products except DCs (P < 0.05) increased in the AUTO-Tx group, whereas they all increased in the ALLO-Tx group (P < 0.01). Protein oxidation parameters also changed significantly (P < 0.01) in the ALLO-Tx group but did not in the AUTO-Tx group (P < 0.05). The differences in PGE2 and LTB4 levels were not significant. Histopathologic examination revealed prominent glomerular and tubular injury in the AUTO-Tx and ALLO-Tx groups but less in the ALLO-Tx + BQ group. In the last group, all parameters of lipid peroxidation (P < 0.001 for all) and PCs decreased, and PSs were preserved (P < 0.001 for both) when compared with the AUTO-Tx and ALLO-Tx groups. We conclude that BQ-123, in addition to inhibiting the binding of ET-1,2 to the ETA receptor, may also inhibit the release and/or synthesis of ET-1,2 and prevent reperfusion injury in kidney transplantation.
Keywords: Animals; Male; Rats; Proteins; Rats, Wistar; Analysis of Variance; Lipid Peroxidation; Malondialdehyde; Reperfusion Injury; Rats, Sprague-Dawley; Transplantation, Autologous; Oxidation-Reduction; Nephrectomy; Dinoprostone; Kidney Transplantation; Endothelin Receptor Antagonists; Leukotriene B4; Peptides, Cyclic; Receptor, Endothelin A; Renal Circulation; Transplantation, Homologous